DELVING INTO EMPLOYEE INNOVATION: THE ROLE OF PERSONALITY AND GOAL SETTING THEORY OF MOTIVATION - M.Subashini, Dr.G.Madhumita (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Innovation is the buzz word in the business organizations from decades. Innovation in the organization is possible with the employees in the organization who behave innovatively; Innovative work behavior leads to innovation. Among the several factors which influences innovative behavior in employees, motivation (intrinsic and extrinsic) plays a vital role. This study is a conceptual framework to understand the effect of goal setting theory of motivation on employee behaviors which leads to innovative work behavior. This paper has identified a set of individual behaviors that correlated with the five principles (Clarity, Challenge, Effort, Feedback, and Task Complexity) of goal setting theory of motivation. The underlying behaviors that are identified are low context communication style, ambitious, broadminded, imaginative and courageous.